Absolutely convergent Fourier–Jacobi series and generalized Lipschitz classes. Issue 4 (3rd April 2023) - Saadi, Faouaz; Daher, Radouan
Abstract : In this paper, we give necessary and sufficient conditions in terms of Fourier–Jacobi coefficients of a function f, to ensure that f belongs either to one of the generalized Lipschitz classes H α, β m and h α, β m for α ≥ β ≥ − 1 / 2 and α ≠ − 1 / 2 . Also a condition for generalized Jacobi differentiability of a function on interval [ 0, π ] is proved.